Development and validation of an earphone-based system to measure short physical performance battery in older adults - Hyeob Choi; Sunghwan Ji; Jinkyuk Kim; Chang Keun Jung; Jaehyung Shin; Yun Jeong Baek; Heyjin Kim; Eun Young Kim; Dae Young Kim; Jae-Young Lim (Experimental Gerontology)
The short physical performance battery (SPPB) is a widely used clinical assessment tool to evaluate physical function in older adults. However, the manual measurement of the SPPB presents difficulties in terms of standardization and accessibility. To address these limitations, an earphone-shaped SPPB assessment device, named B-Lab, was developed. To validate the device, 45 healthy participants aged 60 years and older were recruited, and the SPPB results obtained through the B-Lab were compared with those from the manual method. Results showed high agreement between the two methods, with an intraclass correlation coefficient of 0.87 and 0.68 for the first and second trials, respectively. The reliability of the B-Lab was also comparable to that of the manual method. Overall, the B-Lab showed potential as an alternative for assessing SPPB scores. It enables patients to assess their physical function without hospital visits, and is expected to contribute to the development of a more effective healthcare environment.